Analisis Faktor-Faktor Yang Berhubungan Dengan Kelelahan Fisik Karyawan (Studi Kasus PT. X) - Gita Pati Humairoh; Rama Dani Eka Putra (Fakultas Teknik, 2020)
PT. X is a plant in rubber production. Rubber factories in some material handling activities still use material handling manually and depending on the worker, physical requesting from these workers needs to be considered the factors that influence it. The research objective is to study any factors related to the work of employees in the production department of PT. X. The method used in this study is a cross-sectional study that is research carried out or collected simultaneously at the same time, this is done in order to get the good results. The results in this study obtained factors that have an effect on the physical, sex of employee with physical employee with a value of P value = 0,000 and work intensity of employees with physical employees with a value of P value = 0,000.